Respostas

2014-04-29T18:45:53-03:00
V3/2+1/2=2V3/2 corta-se fica V3
1 5 1
2014-04-29T18:49:40-03:00
Sen²x + cos²x = 1 (V3 / 2)² + cos²x = 1 cos²x = 1 - 3/4 cosx = 1/2 cos² x = 1/4 Eu interpretei a questão da sequinte maneira, pois, está faltando alguns paratenses rsrs: y = (tg² x - secx ) / (cossec² x - 1) y = [(sen²x/cos²x) - (1/cosx)] / [(1/sen²x) - 1] y = [(√3/2)² / (1/2)²] - [1/(1/2)] / {[(1/(√3/2)²] - 1} y = {[(3/4) / (1/4)] - 2} / {[1/(3/4)] - 1} y = (3 - 2) / (4/3 - 1) y = 1 / (1/3) y = 3